2022
DOI: 10.21883/tp.2022.01.52540.217-21
|View full text |Cite
|
Sign up to set email alerts
|

Radar absorbing properties of polyvinyl alcohol/Ni-Znferrite-spinel composite

Abstract: The electromagnetic and radio-absorbing characteristics offerrite-polymer composites with conductive inclusions based on polyvinylalcohol are investigated. The Ni-Zn spinel ferrite powder of 2000NN gradewith composition Ni0.32Zn0.68Fe2O4 was used as filler. It is shown that theobtained composites are effective absorbers in the frequency range of 2-5 GHz with peak reflection loss less than ~20 dB. Through the analysis of thepermittivity spectra and permeability spectra, as well as the calculatedreflection loss … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…We found excellent radar absorption properties of two-component RACs with Ni-Zn and Li-Mn-Zn spinel ferrites at weight fractions of 60-80% (volume concentrations of 25-61%) with Rl = −33.8-−20 dB and an absorption bandwidth of Δf (−10 dB) in the 2-4 GHz range and at 2-7 GHz frequencies [18,55,67]. The matrices were PVDF, PVA and polystyrene.…”
Section: Radar-absorbing Parameters Of Ferrites and Ferrite-polymer C...mentioning
confidence: 83%
See 1 more Smart Citation
“…We found excellent radar absorption properties of two-component RACs with Ni-Zn and Li-Mn-Zn spinel ferrites at weight fractions of 60-80% (volume concentrations of 25-61%) with Rl = −33.8-−20 dB and an absorption bandwidth of Δf (−10 dB) in the 2-4 GHz range and at 2-7 GHz frequencies [18,55,67]. The matrices were PVDF, PVA and polystyrene.…”
Section: Radar-absorbing Parameters Of Ferrites and Ferrite-polymer C...mentioning
confidence: 83%
“…The RAM thickness was 6 mm, the dielectric permeability ε r was within 10 and the magnetic permeability µ r in the sub-resonance region was 500-1000. It was found that the Ni-Zn also has predominantly magnetic loss, with a small fraction of dielectric loss due to hopping polarization [55]. These losses occur in defective ionic bond crystals, which is the case for ferrites with oxygen deficiency after annealing [56].…”
Section: Radar-absorbing Parameters Of Ferrites and Ferrite-polymer C...mentioning
confidence: 99%